Transformasi Struktural Wanita Transmigran dan Kontribusinya terhadap Pendapatan Rumah Tangga: Kasus di Daerah Transmigrasi Sekitar Kotamadya Bengkulu - Ketut Sukiyono; nFN Sriyoto (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 1997)
This research was aimed at identifying motivation influencing off-farm economic activities of transmigrant women and studying their decision making pattern, investigating influencing factors of their structural transformation, and analyzing their contribution on family income. This research was conducted in ex-transmigration area around Kotamadya Bengkulu by interviewing 48 transmigrant women. The results showed that due to high family needs, looking for additional income, low farm income, leissure time utilizing, looking for experience, marginal farm land, small farm land, easeful transportation, transmigrant women are motivated to work out offarm. Women dominated in decision making in all aspects of off-farm woman activities. The results also showed that transmigrant women contribute 45.44 percent to the total family income.